2010
DOI: 10.1016/j.expneurol.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Migration and homing of bone-marrow mononuclear cells in chronic ischemic stroke after intra-arterial injection

Abstract: Cell-based treatments have been considered a promising therapy for neurological diseases. However, currently there are no clinically available methods to monitor whether the transplanted cells reach and remain in the brain. In this study we investigated the feasibility of detecting the distribution and homing of autologous bone-marrow mononuclear cells (BMMCs) labeled with Technetium-99 m ((99m)Tc) in a cell-based therapy clinical study for chronic ischemic stroke. Six male patients (ages 24-65 years) with isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 51 publications
2
85
0
4
Order By: Relevance
“…26 Ten small clinical studies of intravenous or intra-arterial cell delivery, including 136 subjects, have reported findings. [27][28][29][30][31][32][33][34][35][36] The majority of these were small, single-institution safety and tolerability studies. Only three included a control group, and the value of the control groups is questionable, since in many cases they consisted of patients deemed ineligible for the cell therapy intervention, were not randomised, and did not necessarily undergo any study related procedures.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Ten small clinical studies of intravenous or intra-arterial cell delivery, including 136 subjects, have reported findings. [27][28][29][30][31][32][33][34][35][36] The majority of these were small, single-institution safety and tolerability studies. Only three included a control group, and the value of the control groups is questionable, since in many cases they consisted of patients deemed ineligible for the cell therapy intervention, were not randomised, and did not necessarily undergo any study related procedures.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
“…Allocation was not always concealed to either patients or investigators. Piecemeal reporting of studies 24,27,28,34 further confuses the interpretation of these reports. Since the main focus was safety, long time windows for cell administration (between days and several months after stroke) were typically permitted.…”
Section: The Acute or Early Subacute Paradigmmentioning
confidence: 99%
“…105 Sequential imaging in particular may enable the detection of aberrant cell migration and/or proliferation. 106,107 Despite their advantages (cheap, high-throughput), optical/ bioluminescent imaging systems are not suitable for translation into large animal models or the clinic, as they are severely limited by the low penetration of light through tissue of substantial thickness.…”
Section: Translating Cell Tracking Technologies To the Clinicmentioning
confidence: 99%
“…Поскольку хоминг МСК и других стволо-вых клеток в головном мозге ограничен при внутривенной трансплантации, группой бра-зильских исследователей было выполнено внутриартериальное введение 99m Tc -меченных МСК у шести пациентов, перенесших инсульт, с целью добиться возможного увеличения количества клеток, трансплантируемых в го-ловной мозг [23]. Было показано, что хоминг клеток в ишемизированном полушарии на-блюдался уже через 2 ч после развития инсуль-та, однако, хоминг значительно уменьшался через 24 ч после инсульта.…”
Section: мск для терапии инсультаunclassified